STRATEGI PENINGKATAN PRESTASI BELAJAR NAHWU KELAS II ULA DI MADRASAH DINIYAH PONDOK PESANTREN PUTRI AL-LATHIFIYYAH 1 BAHRUL ‘ULUM TAMBAKBERAS JOMBANG - Khiyarotun Ni'mah; Hilyah Ashoumi (Universitas KH. A. Wahab Hasbullah, 2019)
The success of a teaching and learning process will not be separated from the methods and strategies that will be used because teaching strategies are one of the factors that play an important role in the learning process. The type of research the author uses in this research is descriptive qualitative. The results obtained are descriptive results in the form of words. Sources of data in this study are the head of madrasah, waka madrasah, religious teacher and some students. Data collection is done by using methods of observation, interviews, questionnaires and documentation Learning and memorizing required students to achieve an achievement. In Madrasah diniyah Al-Lathifiyyah 1 Bahrul Islamic boarding school ‘Ulum Tambakberas Jombang precisely in nahwu class II Ula lessons. The strategy used by the teacher to improve student achievement is to use interactive strategies in the form of peer tutoring methods, making nahwu resume books, and reading books. The learning achievements achieved by students with the existence of these strategies in the even semester examination in the 2018/2019 learning year. Grade II Ula Madrasah Diniyah students' achievements can be said to be quite satisfying. and the inhibiting factors in increasing the learning achievement of nahwu namely the lack of attention of a teacher while teaching, in addition to that due to the lack of nahwu lessons in madrasah diniyah Al-Lathifiyyah 1. While the supporting factors in increasing learning achievement nahwu namely by the existence of methods and strategies which is used by well teachers.